2016
DOI: 10.1016/j.jdeveco.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The migration response to increasing temperatures

Abstract: SummaryClimate change, especially the warming trend experienced by several countries, could affect agricultural productivity. As a consequence, rural incomes will change, and with them the incentives for people to remain in rural areas. Using data from 116 countries between 1960 and 2000, we analyze the effect of differential warming trends across countries on the probability of either migrating out of the country or from rural to urban areas. We find that higher temperatures increased migration rates to urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
139
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(151 citation statements)
references
References 32 publications
9
139
1
2
Order By: Relevance
“…Applying the inclusion/exclusion criteria yielded 53 papers published from 1989 to 2017, as presented in Figure 1 and Table 1. Four studies examine the environmental change-migration nexus by using data on countries of sub-Saharan Africa (SSA); one paper adopts a broader perspective by focusing on all 116 countries, including SSA (Cattaneo and Peri 2016); and three papers have a special focus on countries in the SSA (Barrios, Bertinelli, and Strobl 2006;Suckall, Fraser, and Forster 2017). There are 22 articles that use a comparative approach dealing with case studies from more than one country.…”
Section: Trends and Geographical Scopementioning
confidence: 99%
“…Applying the inclusion/exclusion criteria yielded 53 papers published from 1989 to 2017, as presented in Figure 1 and Table 1. Four studies examine the environmental change-migration nexus by using data on countries of sub-Saharan Africa (SSA); one paper adopts a broader perspective by focusing on all 116 countries, including SSA (Cattaneo and Peri 2016); and three papers have a special focus on countries in the SSA (Barrios, Bertinelli, and Strobl 2006;Suckall, Fraser, and Forster 2017). There are 22 articles that use a comparative approach dealing with case studies from more than one country.…”
Section: Trends and Geographical Scopementioning
confidence: 99%
“…However, in some poor counties, such as Mali in the mid-1980s, due to the lack of adequate resources to support migration, migration declined relative to past levels [61]. Furthermore, Cattaneo found that temperature rise gradually reduced international migration in some poor countries [62]. By using Mexico and Ethiopia as case studies, employing two different model datasets, considering two decades, and considering Pop and Built-up as control variables, it was found that crop yield deviation was significantly correlated with population redistribution at the country level.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our paper contributes to the nascent literature on migration as an ex-post strategy to mitigate the negative impacts of extreme weather shocks (Bohra-Misra et al 2014;Bryan et al 2014;Cattaneo and Peri 2016;Dillon et al 2011;Gray and Mueller 2012;Grögger and Zylberberg 2016;Halliday 2006;Jessoe et al 2018;Mueller et al 2014;Yang 2008). Because people relocate in response to drops in income, ex-post migration movements tend to take place to nearby locations for short periods, and might not be an option for people with incomes close to subsistence levels (Bryan et al 2014;Cattaneo and Peri 2016;Kleemans 2014;Yang 2008). Our contribution to this literature is twofold.…”
Section: Introductionmentioning
confidence: 93%
“…Migration is a coping strategy used by households if access to financial markets is limited or the support from social networks is not sufficient (Grögger and Zylberberg 2016). After a negative weather shock, households may decide to send some household members to nearby towns to earn additional income or may even take the more radical step to migrate altogether (Bohra-Misra et al 2014;Cattaneo and Peri 2016;Dillon et al 2011;Grögger and Zylberberg 2016;Halliday 2006;Jessoe et al 2018;Kleemans 2014).…”
Section: Migration Weather Shocks and The Legacies Of Rebelocracymentioning
confidence: 99%
See 1 more Smart Citation